Remote ischaemic preconditioning in coronary artery bypass surgery: a meta-analysis. Issue 17 (8th August 2012) - D'Ascenzo, Fabrizio; Cavallero, Erika; Moretti, Claudio; Omedè, Pierluigi; Sciuto, Filippo; Rahman, Ishtiaq A; Bonser, Robert S; Yunseok, Jeon; Wagner, Robert; Freiberger, Tomas; Kunst, Gudrun; Marber, Michael S; et al.
Abstract : Aim: Randomised trials exploring remote ischaemic preconditioning (RIPC) in patients undergoing coronary artery bypass graft (CABG) surgery have yielded conflicting data regarding potential cardiovascular and renal protection, and are individually flawed by small sample size. Methods: Three investigators independently searched the MEDLINE, EMBASE and Cochrane databases to identify randomised trials testing RIPC in patients undergoing CABG. Results: Nine studies with 704 patients were included. Standardised mean difference of troponin I and T release showed a significant decrease (−0.36 (95% CI −0.62 to −0.09)). This difference held true after excluding the trials with cross-clamp fibrillation, the study with off-pump CABG and studies using a flurane as anaesthetic agent (−0.41 (95% CI −0.69 to −0.12), −0.38 (95% CI −0.70 to −0.07) and −0.37 (95% CI −0.63 to −0.12), respectively). A similar trend was also obtained for patients with multivessel disease (−0.41 (95% CI −0.73 to −0.08)). The trials evaluating postoperative creatinine reported a non-significant reduction (0.02 (95% CI −0.09 to 0.13)). Moreover, the length of in-hospital stay was not influenced by the kind of treatment (weighted mean difference 0.27 (95% CI −0.24 to 0.79)). Conclusion: RIPC reduced the release of troponin in patients undergoing CABG. Larger randomised trials are needed to clarify the presence of a causal relationship between RIPC-induced troponin release and clinical adverse events.